IKTVA and Saudi Arabia Vision 2030 - Savio, Raj (Eximia, 2021)
The In-Kingdom Total Value Add (IKTVA) Program, launched in December 2015, is an initiative of Saudi Aramco to drive additional domestic value creation in Saudi Arabia. This was launched in order to support the rapidly changing economic environment and promote future prosperity. It is the bedrock of the strategy at Saudi Aramco, A Saudi Arabian Petroleum and Natural Gas Company that is based in Dhahran. According to Al-Ghalayni, Chairman and CEO of BMG Financial Group, “Made in Saudi Arabia” as a slogan carries the vision and will be crucial to the long-term economic growth of the Kingdom. To date, Saudi Aramco has held 5 Annual IKTVA forums and exhibitions. The 2-day 2020 forum attracted more than 70 exhibitors, 14 government bodies, and 8 international energy players in the industry. This alone was a significant boost to the efforts made locally towards localization of the Kingdom’s economy.